Philosophy in the tatana ethnic Sayau Moginum dance in the Kuala Penyu district, Sabah - Victor B. Pangayan; Resty Cindy Oni Madis; Norhana Nordin; Alan James (Penerbit Universiti Malaysia Sabah, 2024)
The Tatana ethnic group constitutes one of the ethnic minorities in Sabah, predominantly residing in the Kuala Penyu area. Like other indigenous ethnic groups in Sabah, the Tatana ethnic group owns a unique traditional dance. The Sayau Moginum dance stands among the most frequently performed traditional dances. A preliminary analysis indicates that Sayau Moginum is a significant dance within the moginum ceremonies. The results indicate that the performance of Sayau Moginum encompasses the Tatana ethnic philosophy, which underlies the intricate and captivating social structure of this ethnic group. This study is significant in this field as it gathers information on Sayau Moginum performance and may serve as a future reference for the younger generations of the Tatana ethnic group.